Fat, sick, & nearly dead [videorecording (DVD)] - Cross, Joe; Engfehr, Kurt; Staples, Phil (Reboot Media, 2011)
Filmmaker Joe Cross, recently obese and unhealthy, travels the United States promoting to all he encounters a lifestyle "reboot" centered around consuming only fruit and vegetable juices. Along the way he meets Phil Staples, a morbidly obese man to whom Cross offers his reboot cure.